1989
DOI: 10.1002/em.2850130404
|View full text |Cite
|
Sign up to set email alerts
|

Absence of mutagenic interaction between microwaves and mitomycin C in mammalian cells

Abstract: Evidence in the literature from in vitro and in vivo studies as to whether or not radiofrequency radiation (RFR) in the microwave range is mutagenic is predominantly negative, with some positive reports. No evidence is available as to whether RFR will alter the mutagenic activity of genotoxic chemicals during a simultaneous exposure, a likely real-life situation. Two hypotheses have been proposed: a) that RFR by itself can cause mutations in a mammalian cell in vitro assay system; and b) that a simultaneous ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…Several studies (Szmigielski et al, 1982;Scarfi et al, 1996;Maes et al, 1997;Pakhomova et al, 1997) have suggested that microwaves can have an epigenetic effect in vivo, and that they can exacerbate the genotoxicity of ionizing radiation or cancer-inducing substances, or potentiate other epigenetic factors (IEGMP, 2000). However, the evidence for an epigenetic effect of microwaves is equivocal since some studies have failed to reproduce the positive results reported by others (Ciaravino et al, 1987(Ciaravino et al, , 1991Meltz et al, 1989Meltz et al, , 1990Cain et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies (Szmigielski et al, 1982;Scarfi et al, 1996;Maes et al, 1997;Pakhomova et al, 1997) have suggested that microwaves can have an epigenetic effect in vivo, and that they can exacerbate the genotoxicity of ionizing radiation or cancer-inducing substances, or potentiate other epigenetic factors (IEGMP, 2000). However, the evidence for an epigenetic effect of microwaves is equivocal since some studies have failed to reproduce the positive results reported by others (Ciaravino et al, 1987(Ciaravino et al, , 1991Meltz et al, 1989Meltz et al, , 1990Cain et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, cell phone radiation can alter protooncogene activity (Ivaschuk et al, 1997;Goswami et al, 1999). However, a similar number of studies have failed to detect obvious clastogenic effects following microwave irradiation of isolated animal cells in vitro (Alam et al, 1978;Lloyd et al, 1984Lloyd et al, , 1986Wolff et al, 1985;Meltz et al, 1987Meltz et al, , 1989Meltz et al, , 1990Kerbacher et al, 1990;Maes et al, 1997Maes et al, , 2001. Thus, there is still no conclusive answer as to whether exposure to microwaves is clastogenic, i.e., whether they can direct or indirectly increase the frequency of chromosomal aberrations.…”
Section: Introductionmentioning
confidence: 99%
“…Very detailed work in this area has been reported by Meltz et al [1989Meltz et al [ , 1990. In both independently performed series of investigations, L5178Y mouse leukemic cells were exposed to a 2450 MHz pulsed wave signal for 4 h. The mean SARs [30 W/kg in Meltz et al, 1989;40 W/kg in Meltz et al, 1990] were such that the temperature in the medium increased above the initial temperature of 37 8C during the 4 h exposure period. The medium temperature increased to, but did not exceed 38.9 8C.…”
Section: Induction Of Micronucleimentioning
confidence: 99%
“…If any of these steps were altered during or because of the simultaneous chemical and RF exposure, there could be an increase or a decrease in the chemically induced mutation frequency. In addition, two different chemical mutagens were examined, MMC [Meltz et al, 1989] and proflavin . The chemicals act in different ways: the MMC can break DNA strands and induce cross links; the proflavin intercalates between the DNA strands.…”
Section: Induction Of Micronucleimentioning
confidence: 99%
“…Moreover, the numbers of cytokinase blocked cells scored in the controls varied widely among the 12 cows. Meltz et al [1989] investigated whether there is an interaction between exposure of mammalian cells to 2.45 GHz RFEMF and MMC. Cells were derived from the L5178Y mouse leukemia line.…”
Section: Mammalian Live Tissues and Cells Exposed In Vitromentioning
confidence: 99%